KARAKTERISASI SIFAT FISIKA DAN KIMIA CUKA KAYU DARI TANDAN KOSONG KELAPA SAWIT - Karima, Rizka (Jurnal Riset Industri Hasil Hutan, 2014)
Thereâs so many pal solid waste or palm empty fruit bunches, but the utilization is not maximized, this research its to optimized utilization of palm solid waste to be wood vinegar and want to know the composition physical properties and chemical properties of wood vinegar from palm empty fruit bunches. Total yield of wood vinegar from palm empty fruit bunches its 15,94 % and total yield of charcoal its 64,58 %. GCMS result showing chemical properties from wood vinegar of burning < 100oC its obtained 19 compound and burning >100 oC its obtained 6 compound. The result physichal properties testing from crued wood vinegar its obtained specific gravity 1,0005 and 1,0010, pH value are 3,233 and 3,186, TAT content are 9,36 % and 11,12 %, phenol content its 0,44 %. The result physical properties testing from wood vinegar which has decolorizatin by activated carbon its obtained specific gravity are 0,9987 and 0,999, pH value are 3,036 and 3,012, TAT content are 8,29 % and 9,27 % and phenol content its 0,01 %.Keywords: palm bunches, wood vinegar, liquid smoke